Analysis of the Development of the Psychology of Religion About Online Game Addiction in Students at The Elementary School Level - Ulmi Sulistia; Eva Latipah; Suharsono (Insight School Academy, 2023)
The characteristics of a person's development vary, depending on the factors that influence a person's story. The developmental aspects of school-age children differ from those of adolescents and adulthood. This study aims to determine the psychological development of children at the elementary level addicted to online games. This research is classified as qualitative research with a field research approach and data collection techniques obtained from observation, questionnaires, and documentation. Data sources were acquired from students and counseling teachers in class V at SDN Natah Wetan . The data analysis technique uses data triangulation, including data collection ( data collecting ), data reduction ( data reducing), data presentation ( data displaying ), and conclusion . The results of this study state that the characteristics of the development of school-age children include cognitive, physical, language, social, and emotional aspects. Many factors affect development that will cause problems in development. These factors include genetic factors and environmental factors. The process of developing these four aspects sometimes needs fixing.